Energy, exergy and economic analyses for the selection of working fluid and metal oxide nanofluids in a parabolic trough collector. (15th July 2019) - Ehyaei, M.A.; Ahmadi, A.; Assad, M. El Haj; Hachicha, A.A.; Said, Z.
Highlights: Complete energy, exergy and economic analyses in a specified PTC. Calculation of the key parameters of a PTC. Comparison of the results for different basefluids (water and thermal oil VP-I) and metal oxide nanoparticles (Al2 O3 and CuO). Energy and exergy efficiencies of PTC with water as a base fluid are 10.81% and 9.44% and for oil are 10.64% and 9.07, respectively. PTC heat rate gain costs are 0.05 and 0.06 /kWh for water and oil, respectively. Adding 5% volumetric ratio of Al2 O3 and CuO to water increases annual average energy efficiency. Abstract: In this paper, energy, exergy and economic analyses of a parabolic trough solar collector (PTC) are carried out in Tehran (Capital of Iran). Two basefluids (water and thermal oil VP-1) with different volumetric ratios (1%, 3%, and 5%) of CuO and Al2 O3 nanoparticles are investigated. For this purpose, 1-D mathematical model is developed using MATLAB software to simulate the energy and exergy efficiencies of the PTC. The numerical model is first validated with experimental data from literature and a good agreement was obtained. Numerical results show that using water as basefluid has better energy and exergy efficiencies than oil. Annual average energy and exergy efficiencies (10.81% and 9.44%) of PTC using water as a basefluid are higher than those (10.64% and 9.07%) of PTC using oil as a basefluid. Also in general, adding nanoparticles has non-considerable effects on system performance (both basefluids). For example, adding Al2 O3 and CuO with 5% volumetric ratio to water as a basefluid increases annual average energy efficiency 0.03% and 0.09%. But exergy efficiency increases by 1.98% and 0.93%, respectively. Cost of heat rate gain by a PTC is 0.05 and 0.06 /kWh for water and oil, respectively. Also adding nanoparticles to the basefluid does not have a major effect on this cost.